2010
DOI: 10.1097/coh.0b013e32833a0b69
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral drug concentrations in the male and female genital tract: implications for the sexual transmission of HIV

Abstract: There appear to be several patterns of drug penetration into the male and female genital tract. In addition there appear to be different patterns of genital shedding under the influence of antiretroviral therapy. What effect these factors will have on the sexual transmission of HIV or the evolution and transmission of resistant HIV remains to be seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 63 publications
1
41
0
Order By: Relevance
“…This discordance between BP HIV RNA level and SP HIV RNA was close to the mean percentage previously reported (10%) (7). TFV penetration in the male genital tract was variable, and TFV SP AUC 0 -24 values were lower than TFV BP AUC 0 -24 values in 12.9% of the men.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…This discordance between BP HIV RNA level and SP HIV RNA was close to the mean percentage previously reported (10%) (7). TFV penetration in the male genital tract was variable, and TFV SP AUC 0 -24 values were lower than TFV BP AUC 0 -24 values in 12.9% of the men.…”
Section: Discussionsupporting
confidence: 49%
“…However, other studies have described a discordance between HIV BP viral load and SP HIV RNA load (spVL) (4)(5)(6). Thus, despite suppression of HIV replication in BP reflected by undetectable HIV RNA levels, spVL was detectable for some patients receiving cART (7). This discordance suggests a compartmentalization of HIV replication in the male genital tract, where the distribution of antiretroviral drugs could be a determinant of HIV shedding (7).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…The proportion of patients with undetectable bpVL but detectable HIV-RNA levels in seminal plasma (SP) ranged from 3 to 48% (8)(9)(10)(11). The mean proportion of patients with this discordance was estimated at 10% (12,13). A longitudinal study in HIV-1-infected men who have sex with men (MSM) has reported a 7.6% discordance (14).…”
mentioning
confidence: 99%